2021
DOI: 10.9734/jammr/2021/v33i1030906
|View full text |Cite
|
Sign up to set email alerts
|

Age at Menarche, Menstrual Characteristics and Associated Factors among Adolescent Girls in Indigenous Population in Niger Delta Region, Nigeria

Abstract: Aim:Age atmenarchevaries among different populations, and isdependent on interaction between genetic and environmental factors. The aim of this study was to determine the age at menarche, menstrual characteristics and associated factors among adolescent girls in indigenous population in Niger Delta region, Nigeria. Study Design: A cross-sectional study on 903 adolescent school girls from 6 secondary schools in Rivers state selected by multi-staged random sampling technique. Place and Duration of St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Menarche, a crucial marker of female sexual maturation, occurs during the beginning of menstruation. The average age at which menarche began in this study was 13 years, which is comparable to the average age reported by Anikweet al, [11], but lower than the value of 15.58 years reported by Tankoet al, [13]. We also discovered a statistically significant correlation between the age of menarche and the length of the menstrual cycle in this study.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Menarche, a crucial marker of female sexual maturation, occurs during the beginning of menstruation. The average age at which menarche began in this study was 13 years, which is comparable to the average age reported by Anikweet al, [11], but lower than the value of 15.58 years reported by Tankoet al, [13]. We also discovered a statistically significant correlation between the age of menarche and the length of the menstrual cycle in this study.…”
Section: Discussionsupporting
confidence: 73%
“…There exist evidences from some research linking menstrual features to menarche age [9,10,11,12]. According to a cross-sectional study by Dambhare et al [9] to assess the age at menarche and menstrual patterns among schoolage girls in the district of Wardha, Central India, the majority (56.15%) had dysmenorrhoea and (56.16%) had premenstrual syndrome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation